Economic-geographical approach for developing small and medium businesses in central Kazakhstan - Chistyakova, G.N.; Huzsti, Zh.; Chistova, A.A. (Fundamental and Experimental Biology, 2016)
This article defines the specific tasks for the development of small and medium businesses (SMB) in the specific conditions of Central Kazakhstan and projectedthe priority development of the cities of two levels.These cities can become Karaganda, Temirtau, Zhezkazgan, Satpayev, Balkhash.Enhancing the role of small and medium businesses (SMB) in Central Kazakhstan requires the study of world experience and search of the most suitable economic-geographical approaches to solving the problems of development and the territorial organization of the considered sector of the economy. In this regard, the authors consider that the proposed economic-geographical approaches to socio-economic development of the region in conjunction with economic and geographic conditions will bring SMB on the trajectory of substantiated development, which meets the standards of medium and highly developed countries.Conducted workconfirms the relevance of the research results of the economic potential of Central Kazakhstan’s to develop the Concept of small and medium businesses development, since the spatial organization of the territory turns into a major factor of social and economic development.